Retrospective Analysis of Preoperative Embolization of Spinal Tumors - Wilson, M.A.; Cooke, D.L.; Ghodke, B.; Mirza, S.K. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Preoperative embolization of primary and metastatic spinal tumors is often performed to decrease intraoperative blood loss and facilitate surgical resection. The purpose of this study was to evaluate the safety of spinal tumor embolization and the variables that may influence intraoperative blood loss. MATERIALS AND METHODS: A retrospective analysis of 100 spinal tumor embolization procedures was performed. Multiple variables were evaluated with respect to intraoperative blood loss, including tumor pathology, degree of tumor embolization, embolization above/below the levels involved, PVA particle size, surgical approach, and invasiveness. RESULTS: There was 1 significant complication of the 100 embolization procedures performed. Evaluation of the entire set of embolization procedures demonstrated that RCC was associated with increased intraoperative blood loss (P = .009) relative to other tumor types, as were the surgical approach and invasiveness of the surgery performed. No other variables were found to be statistically significant predictors of intraoperative blood loss. Subset analysis of all RCCs demonstrated that complete embolization resulted in decreased blood loss compared with partial embolization (P = .03) and that male sex was associated with increased blood loss (P = .029). CONCLUSIONS: Preoperative embolization of spinal tumors is a safe procedure. Complete embolization of RCCs results in lower intraoperative blood loss compared with partial embolization. The effectiveness of preoperative embolization of non-RCCs is unclear. Using smaller embolic particles and embolizing beyond the levels affected by tumor may not provide added benefit. EBLestimated blood lossGCTgiant cell tumorLRlinear regressionn/anot applicablePVApolyvinyl alcoholRCCrenal cell carcinomaVEGFvascular endothelial growth factor